An SPR imaging immunosensor for leptin determination in blood plasma. Issue 5 (13th January 2021) - Sankiewicz, Anna; Hermanowicz, Adam; Grycz, Artur; Łukaszewski, Zenon; Gorodkiewicz, Ewa
Abstract : The schematic illustration of the biosensor SPRI that is a new promising tool for the determination of leptin concentation. Leptin is a hormone that has a fundamental role in the regulation of feeding and energy balance. Abstract : Leptin is a hormone that has a fundamental role in the regulation of feeding and energy balance. A developed specific SPRi immunosensor for leptin may be a new tool for leptin determination in blood plasma. The immunosensor consists of rabbit anti-leptin antibody immobilized on a gold chip via cysteamine linker, using the EDC/NHS protocol. Non-fluidic array SPRi is used for analytical signal formation. Under optimized conditions, the linear response range of the immunosensor covers concentrations from 0.23 to 5 ng mL −1 . The LOD of the immunosensor is 0.07 ng mL −1, and the LOQ is 0.23 ng mL −1 . The precision of measurement depends on leptin concentration, and is between 9.1% and 2.2%. Recoveries of the leptin spike are between 97% and 110%. The immunosensor and related analytical method were validated by parallel determination of leptin in series of plasma from children suffering from malnutrition and a control group, using Enzyme-Linked Immunosorbent Assay (ELISA) and SPRi. Pearson's correlation coefficient was equal to 0.991. The developed immunosensor and related method are more direct, faster and much simpler than ELISA.